Increasing the Value of Undergraduate Clinical Laboratory Science Programs in Academic Institutions Through Undergraduate Research Programs...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference (CLEC), February 25-27, 2016 in Minneapolis, Minnesota. - Korzun, William J. (Clinical Laboratory Science)
Clinical Laboratory Science (CLS) Programs in academic institutions are under increasing pressure to engage in scholarly activities, obtain grants to support them, and generate external awareness of the institution's status as a research-intensive university. A few years ago, we discovered that many of our undergraduate students, after completing two semesters in our CLS Program, possessed the lab skills that were highly desirable to researchers in other academic units. Consequently, the Department of Clinical Laboratory Sciences, in the School of Allied Health Professions, began participating in, and has successfully received funding from the Undergraduate Research Opportunities Program at Virginia Commonwealth University. This fellowship program provides outstanding undergraduates the chance to make substantial and significant progress on a structured research endeavor during the summer in collaboration with a faculty mentor. These activities have increased the visibility of research efforts within the department and student motivation to complete advanced degrees with research requirements. Outcomes have included presentations at university-wide research symposia, presentations at state professional meetings, co-authorship on peer-reviewed publications, increased requests from the School of Medicine for research collaboration with the CLS Dept., subsequent enrollment in graduate programs, and recognition of departmental accomplishment of the institution's research mission. We have concluded that the investment of faculty time and effort to mentor undergraduate students who are interested in research, has led to an identity for the Department of Clinical Laboratory Sciences as a valuable component of the School of Allied Health Professions and Virginia Commonwealth University.